The logic of occasion - Kerkhoff, Manfred (Estudios de Filosofía, 1999)
In Truth and Method, Gadamer, talking about the occasionality of the work of art, propases a "new logic" in the context of hermeneutics. In this paper, that concept is taken to trace, in the work of Lipps, the thought of occasionality and its corresponding hermeneuticallogic. In this way is rehabilitated Lipps, a philosopher interesting to the kairologic thought.